Antioxidant Potential of Black, Green and Oolong Tea Methanol Extracts - Wahyu Widowati; Tati Herlina; Hana Ratnawati; Gabriella Constantia; I Dewa Gde Sathya Deva; Maesaroh Maesaroh (Biology, Medicine, & Natural Product Chemistry, 2015)
Degenerative diseasesandchronicdiseasesare oftencausedbyoxidativestress. Oxidative stress caused by free radicals. Antixodant as inhibitor are needed to prevent it which is one of antioxidant sources is tea. Tea processinggenerally produce various kinds of teas such as black, green and oolong tea. Tea processing  affect thecontent ofphenolic compounds. The aim of the research is to evaluate phytochemical content, totalphenolic content of blacktea, green tea andoolongtea extracts using catechin, quercetin, kaempferol, myricetin as standard, and to evaluate the antioxidative potency of black tea, green tea and oolong tea extracts compared to catechin, quercetin, kaempferol, myricetin. Phytochemical assay using modified Farnsworth method, the antioxidant activity were measured by  by its 1,1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging activity. Green tea extract contained highest phenolic and flavonoid.  The highest antioxidant activity was green tea extract with IC50=0,487μg/mL. Green tea extract content phenol and flavonoid are higher compared to the other extracts,  green tea extract has the highest antioxidant activity.